Detection of the Origin of the Cystic Artery during Transcatheter Arterial Embolization of Hepatocellular Carcinomas: Comparison of Cone Beam CT and Digital Subtraction Angiography - SEINO, Noritaka; GOKAN, Takehiko; HASHIMOTO, Toshi; HONDA, Minoru; HASHIZUME, Takashi (The Showa University Journal of Medical Sciences, 2009)
In this study, we retrospectively compared the usefulness of cone beam CT (CBCT) with that of digital subtraction angiography (DSA) in the identification of the origin of the cystic artery during arterial embolization for hepatocellular carcinoma. Subjects were sixty-four patients who underwent transcatheter arterial embolization (TAE) for hepatocellular carcinoma, in whom both CBCT and DSA were performed. Two radiologists independently examined CBCT and DSA images, and attempted to identify the origin of the cystic artery in each image. For DSA, en face views were reviewed on the monitor. For CBCT, 5 mm thick horizontal sections were generated using Workstation software, and the MPR method was used for coronary sections. These were then investigated with OsiriX. Of the sixty-four patients, the cystic arterial origin could be identified using DSA in 21 (32.8%) and CBCT in 62 (96.8%). The cystic artery was shown to originate in the proper, right, middle, and left hepatic artery in one, 58, two, and one patient, respectively. These results show that CBCT was more useful than DSA for identifying cystic arterial origin. Therefore CBCT should be positively applied during TAE.